2017
DOI: 10.7717/peerj.3634
|View full text |Cite
|
Sign up to set email alerts
|

Littorally adaptive? Testing the link between habitat, morphology, and reproduction in the intertidal sculpin subfamily Oligocottinae (Pisces: Cottoidea)

Abstract: While intertidal habitats are often productive, species-rich environments, they are also harsh and highly dynamic. Organisms that live in these habitats must possess morphological and physiological adaptations that enable them to do so. Intertidal fishes are generally small, often lack scales, and the diverse families represented in intertidal habitats often show convergence into a few general body shapes. However, few studies have quantified the relationship between phenotypes and intertidal living. Likewise,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 70 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…The diet of these fishes is dominated by algae (constituting up to 100% of the stomach contents (see Johnston 1954 ) and their jaws are greatly reduced in length (see Fig. 5 and discussion in Buser et al. 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diet of these fishes is dominated by algae (constituting up to 100% of the stomach contents (see Johnston 1954 ) and their jaws are greatly reduced in length (see Fig. 5 and discussion in Buser et al. 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…S1). Buser et al (2017) identified morphological variation between the species, such as body depth, eye size, and shape, but these morphological characteristics are difficult to discern in the field, especially in females.…”
Section: Species Identificationmentioning
confidence: 99%
“…Species with IGA share several characteristics with true internal fertilizers. For example, most IGA species have a well-developed genital papilla for mating (Evans and Meisner, 2009) and have sperm with elongated head, in comparison with external fertilizing species that lack copulatory anatomy and exhibit round sperm head morphology (Koya et al, 2011;Buser et al, 2017;Ito and Awata, 2019;Ito et al, 2022). While IGA is interesting in the evolution of reproductive strategy, it is currently unknown how widespread this strategy is within Agonidae and Psychrolutidae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A less studied intromittent organ is the ventrally located papillae of male marine, internally inseminating fish species, and to our knowledge, has only been studied in clinid fishes (Clinidae, Blennioidei;Fishelson et al, 2006). Additionally, despite their documentation, marine fish papillae have not been thoroughly investigated in some sculpins in the family Cottidae (Buser et al, 2017), rockfishes in the genus Sebastes (F. R. Shaw et al, 2012), clingfishes in the family Gobiesocidae (Conway et al, 2019), or surfperches (Embiotocidae; Carlisle et al, 1960;Nakazono et al, 1981;E. Shaw, 1971;F.…”
Section: Introductionmentioning
confidence: 99%